Titania And Oberon In William Shakespeare's A Midsummer Night's Dream: An Archetypal View - Wijaya, Herlin Candra; Jati, Ariya (Syntax Literate, 2025)
William Shakespeare's A Midsummer Night’s Dream presents intricate archetypes. The writer is interested in archetypes presented in literary works. The writer would like to classify archetypes presented in William Shakespeare's A Midsummer Night's Dream, one of his literary works. In order to classify the archetypes, the writer adopts Carl Gustav Jung's concept of archetypes and Richard Taylor elements of drama, and she applies Belsey's method of textual analysis. The writer analysis comes into three stages: (1) characterization of Titania and Oberon (2) classifications of their archetype (3) Relationship between the characterization and archetype classification of Titania and Oberon. The analysis results in complexity in Oberon's relationship to Titania. It is expected that the writer's study beneficial for any reader in English literature especially Shakespeare's drama, and in general student of Department of English in particular.